Application of microscopy technology in thermo-catalytic methane decomposition to hydrogen - Mei, I.L.S. (American Institute of Physics Inc., 2015)
Hydrogen production from the direct thermo-catalytic decomposition of methane is a promising alternative for clean fuel production because it produces pure hydrogen without any CO x emissions. However, thermal decomposition of methane can hardly be of any practical and empirical interest in the industry unless highly efficient and effective catalysts, in terms of both specific activity and operational lifetime have been developed. In this work, bimetallic Ni-Pd on gamma alumina support have been developed for methane cracking process by using co-precipitation and incipient wetness impregnation method. The calcined catalysts were characterized to determine their morphologies and physico-chemical properties by using Brunauer-Emmett-Teller method, Field Emission Scanning Electron Microscopy, Energy-dispersive X-ray spectroscopy and Thermogravimetric Analysis. The results suggested that that the catalyst which is prepared by the co-precipitation method exhibits homogeneous morphology, higher surface area, have uniform nickel and palladium dispersion and higher thermal stability as compared to the catalyst which is prepared by wet impregnation method. This characteristics are significant to avoid deactivation of the catalysts due to sintering and carbon deposition during methane cracking process. Â© 2015 AIP Publishing LLC.